1984
DOI: 10.1029/ja089ia08p06579
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary flow systems associated with cosmic ray modulation in 1977–1980

Abstract: The hydromagnetic flog configurations assooiated with the cosmic ray modulation in 197'-1980 were determined using solar wind plasma and magnetic field data from Voyagers 1 and 2 and Helios 1. The modulation was related to two types of large-scale systems of flows: one containing a number of transients such as shocks, post-shook flows and magnetic clouds, the other consisting pr;Lmarily of a series of quasi-stationary flows following interaction regions containing a stream interface and often bounded by a forw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 42 publications
3
85
0
Order By: Relevance
“…Burlaga et al 1984;Cane 2000). Differences between the shock-associated and no-shock events were studied by Badruddin et al (1986) and Badruddin (1996).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Burlaga et al 1984;Cane 2000). Differences between the shock-associated and no-shock events were studied by Badruddin et al (1986) and Badruddin (1996).…”
Section: Methodsmentioning
confidence: 99%
“…First, the data set was sorted by the type of SWD, i.e., a distinction was made between interplanetary coronal mass ejections (ICME), corotating interaction regions (CIR), and mixed ICME-CIR disturbances (mixed). The distinction between ICMEs and CIRs was made following Burlaga et al (1984), Richardson et al (1996), Cane (2000) and Richardson (2004), whereas the events that showed characteristics of both were denoted as mixed events. Examples of ICME-, CIR-, and mixed-events are presented in Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relations between FD magnitudes and the solar wind IMF (Barden, 1973;Iucci et al, 1979a, b;Burlaga et al, 1984;Cane, 1993) and solar wind velocity (Iucci et al, 1979a, b;Belov and Ivanov, 1997) have been studied since long, but the magnitude of the FD and the interplanetary magnetic field (IMF) or the proton velocity V alone have not correlated well. Several studies have shown improved correlations when both the field B and speed V are simultaneously considered.…”
Section: Introductionmentioning
confidence: 99%
“…During the past three decades, modulation research has been primarily focused on understanding and specifying the roles of two of these termsdiffusion and curvature/gradient drift: (1) In the diffusion-centered view, modulation results from the outward propagation, at the solar wind speed, of large steplike decreases in the GCR intensity (McDonald et al 1981;cf., Morrison 1956, andLockwood 1960). The disturbances responsible for these decreases came to be called "merged interaction regions" (MIRs) or "global merged interaction regions" (GMIRs; Burlaga et al 1984Burlaga et al , 1985Burlaga et al , 1993). (2) Alternatively, the approach championed by Jokipii and colleagues (Jokipii et al 1977;Jokipii and Thomas 1981;Kota and Jokipii 1(83) stresses the importance of curvature and gradient drifts of GCRs in the large-scale field of the heliosphere.…”
Section: Introductionmentioning
confidence: 99%